2014
DOI: 10.1155/2014/747415
|View full text |Cite
|
Sign up to set email alerts
|

KML001, a Telomere-Targeting Drug, Sensitizes Glioblastoma Cells to Temozolomide Chemotherapy and Radiotherapy through DNA Damage and Apoptosis

Abstract: Standard treatment for glioblastoma comprises surgical resection, chemotherapy with temozolomide, and radiotherapy. Nevertheless, majority of glioblastoma patients have recurrence from resistance to the cytotoxic conventional therapies. We examined combinational effects of KML001, an arsenic compound targeting telomeres of chromosomes with temozolomide or irradiation, in glioblastoma cell lines and xenograft models, to overcome the therapeutic limitation of chemoradiation therapy for glioblastoma. Although KML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Previous studies have demonstrated that antileukemia activity of KML001 is mainly due to its ability to induce apoptosis and cell cycle arrest via regulation of MAPK and PI3K pathways or telomere shortening (6,24). Also, our study showed that KML001 induced apoptosis both in CCRF-CEM and Molt-4 cell lines.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have demonstrated that antileukemia activity of KML001 is mainly due to its ability to induce apoptosis and cell cycle arrest via regulation of MAPK and PI3K pathways or telomere shortening (6,24). Also, our study showed that KML001 induced apoptosis both in CCRF-CEM and Molt-4 cell lines.…”
Section: Discussionsupporting
confidence: 69%
“…To overcome the barrier, current studies concentrate on combinations with other agents and on development of novel molecular targeting agents . Recently, improvement of TMZ resistance on GMB was reported largely . For example, a varies of microRNAs and agents were found to enhance the sensitivity of GBM to TMZ .…”
Section: Discussionmentioning
confidence: 99%
“…This improved effect resulted marginally synergistic. Since IDE appears to enhance the cytotoxic effects of TMZ, this novel combination for GB therapy merits further investigation, especially as combinations of other drugs and natural compounds with TMZ are being explored continuously (27,31,(35)(36)(37)(38)(39)(40). OX has been occasionally used for treating GB but limited due to its side effects (41).…”
Section: Discussionmentioning
confidence: 99%